The Spatial Distribution and Genetic Diversity of the Soybean Cyst Nematode, Heterodera glycines, in China: It Is Time to Take Measures to Control Soybean Cyst Nematode - Lian, Yun; Koch, Georg; Bo, Dexin; Wang, Jinshe; Nguyen, Henry T.; Li, Chun; Lu, Weiguo (Frontiers in Plant Science, 2022)
The continuous evolution and spread of virulent forms of the soybean cyst nematode (SCN) driven by the environment and anthropogenic intervention is a serious threat to the soybean production throughout the world and including China. Especially in China, the implemented measures to control SCN are insufficient for a sustainable agricultural development yet. We summarize our knowledge about the spread and spatial distribution of SCN in China, and the virulence diversity in the main soybean growing areas. To reveal the genetic relatedness and diversity of SCN populations, we re-sequenced 53 SCN genomes from the Huang-Huai Valleys, one of the two main soybean growing areas in China. We identified spreading patterns linked to the local agroecosystems and topographies. Moreover, we disclose first evidence for selection of complex virulence in the field even under low selection pressure in an example from North Shanxi. SCN is present in all soybean growing areas in China but SCN susceptible cultivars are still largely grown indicating that SCN related damage and financial loss have not received the attention they deserve yet. To prevent increasing yield losses and to improve acceptance for resistant cultivars by the growers, we emphasize it is time to accelerate SCN resistance breeding, planting resistant cultivars to a larger extent, and to support farmers to implement a wider crop rotation for a sustainable development of the soybean production in China.